Upper Gastrointestinal Stent - Kim, Sang Gyun (The Korean Society of Gastrointestinal Endoscopy, 2012)
Gastrointestinal (GI) stent has been developed for palliation of obstructive symptoms in various diseases causing obstruction of GI tract. Self-expanding metal stent (SEMS) has replaced old type of plastic stent, and endoscopic insertion of stent has replaced fluoroscopy-guided insertion. Nowadays, newly-designed SEMSs have been developed for prevention of complications such as stent migration and re-obstruction, and indications of stent recently have been widened into benign conditions as well as malignant obstruction. In this review, the types, method of insertion, indications and clinical outcomes of stent in the upper GI tract would be discussed.